Effects of chemical topping on cotton development, yield and quality in the Yellow River Valley of China - Ling-xiao ZHU; Lian-tao LIU; Hong-chun SUN; Yong-jiang ZHANG; Ke ZHANG; Zhi-ying BAI; An-chang LI; He-zhong DONG; Cun-dong LI (Journal of Integrative Agriculture, 2022)
Topping is a cultivation method that is widely practiced due to the indeterminate growth character of cotton (Gossypium hirsutum L.). Among the different methods of accomplishing topping, manual topping is common in the Yellow River Valley of China, although it is time- and labor-intensive. The objective of this study was to characterize the responses of cotton to different topping treatments with respect to development, yield and quality. This study included field experiments from 2015 to 2016 with three different topping methods: manual topping (MT), chemical topping (CT) using mepiquat chloride, and a non-decapitation treatment (NT). We found that the plant height, the number of fruiting branches and the length of upper fruiting branches of cotton treated with CT were significantly lower than NT. The chlorophyll content of cotton treated with CT was not significantly different from NT, but was higher than that of MT in the later season. CT enhanced plant development with reduced endogenous gibberellic acid and abscisic acid contents, and the apical development of the main stem was inhibited. Compared with MT, CT significantly increased the biomass of the vegetative parts. Most importantly, there were no significant differences in the yield or fiber quality between MT and CT. These findings suggested that CT, a simplified and effective topping method, could be utilized as an alternative in the Yellow River Valley of China.